Baseline layout and design of a 0.8 GW reference wind farm in the North Sea. Issue 9 (29th May 2017) - Bak, Thomas; Graham, Angus; Sapronova, Alla; Florian, Mihai; Dalsgaard Sørensen, John; Knudsen, Torben; Hou, Peng; Chen, Zhe
Abstract: The paper presents a model of a reference wind farm. The model considers the wind and wave climatologies for a specific site from which two different wind farm layouts are derived. These layouts are examined through the effective wake‐enhanced turbulence intensity at the hub height for a given climatology, and a simple model for the influence on capital expenditures is proposed. An electrical design is presented, the cable losses are calculated and the energy yield is determined. An operation and maintenance model is established, and the associated operating expenditure is obtained. All of the models are then summarized in terms of a levelized cost of energy using a numerical simulation tool, which allows the layouts to be compared. The data and models are freely available online for others to use and may serve as a baseline for benchmarking and allow researchers to compare and discuss their results. Copyright © 2017 John Wiley & Sons, Ltd.